1990
DOI: 10.1128/mcb.10.8.4271
|View full text |Cite
|
Sign up to set email alerts
|

M-CAT binding factor, a novel trans-acting factor governing muscle-specific transcription.

Abstract: The cardiac troponin T (cTNT) promoter contains a highly muscle specific distal promoter element capable of conferring muscle-specific transcription from a heterologous TATA box-transcription initiation site.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
111
0

Year Published

1992
1992
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(113 citation statements)
references
References 55 publications
2
111
0
Order By: Relevance
“…However, not all muscle genes contain functional E boxes in their regulatory promoter regions, and myogenic bHLH proteins can also activate transcription of muscle-specific genes that lack E boxes in their control regions (3). As expected, from these data, other muscle-specific transcription factors have been described to function as intermediates in the activation of gene expression during myogenesis, such as the M-CAT binding factor (11), and the myocyte enhancer factor 2 (MEF2) (12,13).…”
mentioning
confidence: 79%
“…However, not all muscle genes contain functional E boxes in their regulatory promoter regions, and myogenic bHLH proteins can also activate transcription of muscle-specific genes that lack E boxes in their control regions (3). As expected, from these data, other muscle-specific transcription factors have been described to function as intermediates in the activation of gene expression during myogenesis, such as the M-CAT binding factor (11), and the myocyte enhancer factor 2 (MEF2) (12,13).…”
mentioning
confidence: 79%
“…Differentiation of cardiac muscle progenitor cells involves the selective activation of the GATA4 and Nkx2.5 transcription factors in pluripotent mesoderm (18 -20). However, because mutation of TEF-1 binding sequences in the promoters of cardiac-specific genes causes a loss of tissue specificity (2), and because ablation of TEF-1 expression causes abnormal cardiac development and an embryonic lethal phenotype (21), these studies support a role for TEF-1 factors in cardiac development. In the adult, cardiac myocytes respond to growth-promoting stimuli by undergoing hypertrophy, rather than cell division.…”
mentioning
confidence: 86%
“…Cardiac troponin T is expressed in fetal skeletal muscle and in cardiac muscle. Mutation analysis of the cardiac troponin T promoter showed that the MCAT element (originally defined as a muscle-specific cytidine-adenosine-thymidine sequence, 5Ј-CATTCCT-3Ј) is required for high levels of promoter activity in cardiac and skeletal muscle cells (1,2). Similar MCAT elements have been characterized in a large number of skeletal and cardiac muscle-specific promoters (3).…”
mentioning
confidence: 93%
“…Nuclear extracts were prepared from tissue culture cells as described previously (28). Breast muscle from 13-day chicken embryos was dissected, and nuclei isolated were as described by Mar and Ordahl (46). Extracts Nucleotide sequence accession number.…”
Section: Materuils and Methodsmentioning
confidence: 99%